Twenty Decisive Battles of the World - Mitchell, Joseph B. and Creasy, Edward S. (New York Konecky & Konecky, 1964)
Includes material on the battles of Marathon, Syracuse, Arbela, the Metaurus, Teutoburger Wold, Ch^alons, Tours, Hastings, Orleans, the Armada, Blenheim, Poltava, Saratoga, Valmy, Waterloo, Vicksburg, Sadowa, First Marne, Midway, and Stalingrad.
Include Maps, Bibliography and Index
Keywords: Battles